2017
DOI: 10.1002/mds.27183
|View full text |Cite
|
Sign up to set email alerts
|

11C‐PE2I and 18F‐Dopa PET for assessing progression rate in Parkinson's: A longitudinal study

Abstract: Striatal C-PE2I appears to show greater sensitivity for detecting differences in motor severity than F-dopa. Furthermore, dopamine transporter decline is closely associated with motor progression over time, whereas no such relationship was found with aromatic l-amino acid decarboxylase. C-PE2I may be more effective for evaluating the efficacy of neuroprotective treatments in PD. © 2017 International Parkinson and Movement Disorder Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
48
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 73 publications
3
48
1
Order By: Relevance
“…In particular, the dopamine transporter (DAT) ligand 11 C-PE2I seemed to have a greater predictive value and sensitivity for detecting differences in motor impairment than AADC imaging using 18 F-DOPA. Furthermore, DAT decline seemed to be closely associated with the decline in motor progression over time, whereas no such relationship was found with AADC, suggesting that 11 C-PE2I is a more objective biomarker than 18 F-Dopa for investigating the effects of novel interventions 24 .…”
Section: Imaging In Transeuromentioning
confidence: 91%
“…In particular, the dopamine transporter (DAT) ligand 11 C-PE2I seemed to have a greater predictive value and sensitivity for detecting differences in motor impairment than AADC imaging using 18 F-DOPA. Furthermore, DAT decline seemed to be closely associated with the decline in motor progression over time, whereas no such relationship was found with AADC, suggesting that 11 C-PE2I is a more objective biomarker than 18 F-Dopa for investigating the effects of novel interventions 24 .…”
Section: Imaging In Transeuromentioning
confidence: 91%
“…123 I-FP-CIT SPECT was performed during screening visits using standardized imaging were first rigid registered to an in-house custom DAT template created from a series of thirty-three 11 C-PE2I positron emission tomography scans, [8] which is a radioligand with high specificity for DAT. [9,10] Registered 123 I-FP-CIT images were then spatially normalized to this DAT template using 12-parameter affine registration and non-linear warping procedure in SPM12 (Statistical Parametric Mapping, Wellcome Trust Centre for Neuroimaging, London, UK).…”
mentioning
confidence: 99%
“…These results revealed that [ 3 H]WIN 35,428 (Figure ) was a far more effective radioligand than cocaine due to the slower dissociation rate of the ligand–protein complex, and this has made [ 3 H]WIN 35,428 the most widely used radioligand for characterization of DAT in vitro. Another tropane derivative, PE2I (Figure ), which is used extensively as a PET imaging agent to localize DAT, has been found to be at least as potent as WIN 35,428, but it has an even slower off‐rate . All of the numerous other studies with DAT‐specific tropane derivatives have focused on the determination of ligand affinity using conventional binding assays.…”
Section: Figurementioning
confidence: 99%